Evaluation of Pathology Results of Patients with a History of Breast Cancer who were Operated on for Gynecological Pathologies or Prophylaxis - Yalcin, Necim; Ureyen, Isin; Alci, Aysun; Gokkaya, Mustafa; Kahraman, Alper; Sel, Gorker; Ekin Sari , Gulsum; Toptaş, Tayfun (Gynecology Obstetrics & Reproductive Medicine, 2024)
Objectives: The present study aimed to evaluate the operation results of patients who were followed up due to breast cancer and were operated on due to gynecological pathologies or for prophylactic purposes, and determine the distribution of gynecological pathologies in breast cancer patients Study design: Patients with breast cancer who had gynecological surgery in our institution between December 2015 and January 2023 were retrospectively analyzed in this cross-sectional study. The pathological reports and medical records of the included patients were obtained from the gynecologic oncology electronic database system and the patient files. The study is approved by the institution’s local ethics committee. Results: Totally 57 patients with a history of breast cancer had gynecological operations between December 2015 and January 2023. The median age of the patients was 49. Benign pathologies were detected in the majority of patients with a history of breast cancer, this rate was found to be 87.7%. The pathology revealed malignant/premalignant disease in seven (12.2%) patients. Among these seven patients, four patients had malignant disease one patient had microinvasive cervical cancer, one patient had ovarian serous cancer, one patient had cervical and ovarian metastasis of breast cancer, and one patient had ovarian metastasis of breast cancer. Conclusions: Patients with a history of breast cancer have increased rates of gynecological pathology development compared to the normal population.